2011
DOI: 10.1007/s11483-011-9243-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of State/Phase Transitions on Ice Recrystallization in Atlantic Salmon (Salmo salar) During Frozen Storage

Abstract: Temperature fluctuations during storage and distribution of frozen foods lead to ice recrystallization and microstructural modifications that can affect food quality. Low temperature transitions may occur in frozen foods due to temperature fluctuations, resulting in less viscous and partially melted food matrices. This study systematically investigated the influence of state/phase transitions and temperature fluctuations on ice recrystallization during the frozen storage of salmon fillets. Using a modulated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…Enlargement of ice crystals, damages the internal fibrous structure of potatoes, and ultimately degrades the quality and reduces the storage life. A similar crystal growth was reported by Syamaladevi et al (2012) for frozen salmon and Ablett et al (2002) for frozen sugar solutions. Syamaladevi et al (2012) also reported that when the ice crystal size increases, the number of ice crystals decreased in salmon.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Enlargement of ice crystals, damages the internal fibrous structure of potatoes, and ultimately degrades the quality and reduces the storage life. A similar crystal growth was reported by Syamaladevi et al (2012) for frozen salmon and Ablett et al (2002) for frozen sugar solutions. Syamaladevi et al (2012) also reported that when the ice crystal size increases, the number of ice crystals decreased in salmon.…”
Section: Resultssupporting
confidence: 83%
“…The transition of food from glassy to rubbery state and vice versa is unavoidable under freeze/ thaw conditions. The increased molecular mobility in rubbery state results in the enlargement of crystals and subsequent quality degradation (Syamaladevi, Kalehiwot, Balasigam, & Sablani, 2012). Glassy and rubbery states are important in frozen foods as the reactions are reduced to a large extent in the glassy state (Hagiwara, Mao, Suzuki, & Takai, 2005;Syamaladevi, Sablani, Tang, Powers, & Swanson, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a significant change of color (P \ 0.05) with storage time in the glassy state. This indicates that changes in the quality of food can occur, even when it is stored at a temperature below T g 0 , probably due to occurring enthalpy relaxation over time (Syamaladevi et al 2012). …”
Section: Results and Discussion Colormentioning
confidence: 99%
“…This indicates that diffusion-limited reactions do not completely cease in the glassy state. Enthalpy relaxations may occur in frozen mangoes in the glassy state, resulting in molecular rearrangements and the diffusion of unfrozen water (Syamaladevi et al 2012). This may cause the growth of ice crystals through recrystallization during storage and further stress the fragile cellular structures of mangoes.…”
Section: Hardnessmentioning
confidence: 99%